2017
DOI: 10.1016/j.clon.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia-optimised Intensity-modulated Radiotherapy Techniques in Pharyngeal Cancers: Is Anyone Going to Swallow it?

Abstract: Dysphagia after primary chemoradiotherapy or radiation alone in pharyngeal cancers can have a devastating impact on a patient's physical, social and emotional state. Establishing and validating efficient dysphagia-optimised radiotherapy techniques is, therefore, of paramount importance in an era where health-related quality of life measures are increasingly influential determinants of curative management strategies, particularly as the incidence of good prognosis, human papillomavirus-driven pharyngeal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
(40 reference statements)
3
16
0
1
Order By: Relevance
“…As the burden associated with reduced swallow and speech function has been recognised [6], research has begun to explore how particular oncological and surgical treatment interventions may reduce impact on function [7,8]. This has included reducing toxicity to structures involved in the mechanism of swallow [9], and surgical approaches to limit motor and sensory dysfunction [10]. Similarly, swallow research has explored ways rehabilitation interventions can improve swallow physiology, involving postural adaptations, techniques to improve swallow competence such as swallow manoeuvres by directing food or drink via intact musculature rather than anatomy that may have been altered by disease or surgery [11], respiratory swallowing coordination [12] and expiratory muscle strength training [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As the burden associated with reduced swallow and speech function has been recognised [6], research has begun to explore how particular oncological and surgical treatment interventions may reduce impact on function [7,8]. This has included reducing toxicity to structures involved in the mechanism of swallow [9], and surgical approaches to limit motor and sensory dysfunction [10]. Similarly, swallow research has explored ways rehabilitation interventions can improve swallow physiology, involving postural adaptations, techniques to improve swallow competence such as swallow manoeuvres by directing food or drink via intact musculature rather than anatomy that may have been altered by disease or surgery [11], respiratory swallowing coordination [12] and expiratory muscle strength training [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous systematic reviews have reported on the impact of dose to dysphagia and aspiration structures on dysphagia. This evidence is outdated due to new literature in this area.…”
Section: Introductionmentioning
confidence: 99%
“…While both 3D and intensitymodulated techniques define structures in 3D, the major differences are the degree of conformity, dose to normal tissue, and capability of IMRT to have dose variation within a field whereas 3D conformal within field dose is homogenous. 12 Previous systematic reviews [13][14][15][16][17][18] have reported on the impact of dose to dysphagia and aspiration structures on dysphagia. This evidence is outdated due to new literature in this area.…”
Section: Introductionmentioning
confidence: 99%
“…More recently research has centred on developing models to predict the swallowing function following radiotherapy [ 27 , 28 , 29 ]. The dependence of late swallowing function on various intuitive swallowing OARs, including the pharyngeal constrictor muscles and the potential for modest reductions in the incidence of late swallowing problems by reducing the dose to these structures, has been examined by modelling studies and is being examined in an ongoing randomised trial [ 10 , 30 ].…”
Section: Oral Cavity Oar Definitionmentioning
confidence: 99%